Prognostic Significance of the Systemic Immune-Inflammation Index (SII) in Patients With Small Cell Lung Cancer: A Meta-Analysis - Zhou, Yuting; Shen, Cuifen; Sun, Yu (Frontiers in Oncology, 2022)
Background: Previous studies have investigated the prognostic value of the systemic immune-inflammation index (SII) in small cell lung cancer (SCLC). However, the results have been inconsistent. The study aimed to investigate the prognostic and clinicopathological significance of SII in SCLC through a meta-analysis. Methods: The PubMed, Web of Science, Embase, Cochrane Library, and China National Knowledge Infrastructure databases were thoroughly searched. The pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated to evaluate the prognostic value of the SII for survival outcomes. The combined odds ratios (ORs) and 95% CIs were used to evaluate the correlation between SII and clinicopathological features. Results: Eight studies comprising 2,267 patients were included in the meta-analysis. Pooled analyses indicated that a high SII was significantly associated with worse overall survival (OS) (HR=1.52, 95% CI=1.15–2.00, p=0.003) but not progression-free survival (HR=1.38, 95% CI=0.81–2.35, p=0.238) in patients with SCLC. Moreover, a high SII was associated with extensive-stage SCLC (OR=2.43, 95% CI=1.86–3.17, p<0.001). However, there was a non-significant correlation between SII and age, sex, smoking history, Karnofsky Performance Status score, or initial therapeutic response. Conclusion: Our meta-analysis demonstrated that a high SII could be an efficient prognostic indicator of OS in SCLC. We recommend adopting SII to predict OS in patients with SCLC, and SII in combination with other parameters or biomarkers may aid in addressing the clinical strategy and choosing the best treatment for an individual patient.